МОДЕРНИЗАЦИИ ТРАДИЦИОННОГО ОБЩЕСТВА И ПОЛИТИЗАЦИИ ИСЛАМА В ЕГИПТЕ (вторая половина XIX ñ начало XX в.) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of early modernization of the traditional Egyptian society under strengthening pressure of European countries on Egypt. Greate attention is paid to the development of modern political culture and the response of the Islam on the European threats. In the conclusion the author thinks that the modernization process and slow cecularization has not weakend the Islamic influence in Egyptian society. Moreover Islamic political activity in Egypt has incresed considerably by the early twentieth century.